EFEKTIVITAS PERMAINAN TRADISIONAL DALAM MENINGKATKAN KECERDASAN INTERPERSONAL PADA ANAK USIA DINI - Amelia Putri Stefany; Tari Mahmuda; Rozzana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Early childhood education is the initial stage of education. Current education is a coaching effort aimed at children from birth to six years of age and is carried out with stimulation. One intelligence that is very important to instill from childhood is interpersonal intelligence. This intelligence will ultimately be used in building, cultivating and establishing social relationships with the people around them, such as teachers, peers, family or new people. One of the traditional games to improve cooperative abilities or behavior in early childhood is the traditional game of clogs. clogs play a very important role in improving interpersonal intelligence. In this game, children must interact, coordinate and work together with their friends. Children are trained